Long-term result after operative correction of funnel chest. Issue 1 (January 1971) - Borgeskov, Sven; Raahave, Dennis
Abstract : During the last decades it has been commonly accepted that funnel chest is such a serious cosmetic handicap that it deserves correction for this reason alone. A group of patients with this deformity, operated upon by the method of Paltia (transsternal fixation with metal struts), was re-examined 5 to 10 years postoperatively. In more than 50% of the cases the immediate acceptable cosmetic result had disappeared in contrast to the satisfaction expressed by almost all the patients. Because of the high incidence of recurrence and because of various risks involved in this operation, the authors do not advocate its performance.